2022
DOI: 10.1186/s12879-022-07562-5
|View full text |Cite
|
Sign up to set email alerts
|

Viral pathogens of acute gastroenteritis in Egyptian children: role of the parechovirus

Abstract: Background and aim Human parechovirus (HPeV) has emerged as a pathogen associated with acute gastroenteritis (AGE). Aim To detect the presence of HPeV in the stool samples from Egyptian children with AGE seeking care and the possibility of its co-infection with other enteric viruses. Methodology One hundred stool samples were collected from children attending Mansoura University Children's Hospital wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(67 reference statements)
1
5
1
Order By: Relevance
“…Phylogenetic analyses assigned all study viruses to the HPeV A and specifically to the specific genotypes HPeV A-1, A-4, A-5, A-10, A-14, A-15, A-17, and A-18. This is consistent with the fact that HPeV is known to have the highest genetic diversity in Africa [ 30 , 31 , 33 , 34 ]. However, given that a proportion (9/22) of HPeV-positive samples failed to amplify by nested PCR, as in other studies, it cannot be excluded that a higher number of HPeV genotypes co-circulate in Cameroon, so far without known associated epidemics.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Phylogenetic analyses assigned all study viruses to the HPeV A and specifically to the specific genotypes HPeV A-1, A-4, A-5, A-10, A-14, A-15, A-17, and A-18. This is consistent with the fact that HPeV is known to have the highest genetic diversity in Africa [ 30 , 31 , 33 , 34 ]. However, given that a proportion (9/22) of HPeV-positive samples failed to amplify by nested PCR, as in other studies, it cannot be excluded that a higher number of HPeV genotypes co-circulate in Cameroon, so far without known associated epidemics.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, some previous studies reported higher HPeV detection prevalence than those described here. Studies conducted in Malawi, Ghana and Egypt showed HPeV prevalences as high as 57% (427/749), 24% (164/682) and 19% (19/100), respectively; confirming that HPeV circulation may be intensive in some African countries [ 31 , 32 , 48 ]. Variations in the HPeV prevalences between studies could be explained by differences in the socio-demographic and hygienic conditions that may favour or limit enteric virus transmission between specific populations in different epidemiological settings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, there was no statistically significant association between HPeV‐A infection and the risk of gastroenteritis 38 . In other studies conducted in children with AG, the percentage observed was lower than that obtained in the present study, as in Thailand and Egypt, with detection rates of 14.6% and 19%, respectively 39,40 …”
Section: Discussioncontrasting
confidence: 80%
“…38 In other studies conducted in children with AG, the percentage observed was lower than that obtained in the present study, as in Thailand and Egypt, with detection rates of 14.6% and 19%, respectively. 39,40 Two samples from this study were classified as recombinant strains involving three types of HPeV, namely 4, 17, and 5. This finding had already been reported by Leal et al (2019) in samples from the rural area of northern Brazil.…”
Section: Especie (%) Sorotype N Of Positive Samples (%)mentioning
confidence: 99%